Perspectives on public and private sector and students' choice of career - Leiv OPSTAD (Social Sciences and Education Research Review)
This study investigates students' perceptions of the public sector and examines how these views influence their career preferences. Data were collected via a questionnaire distributed to 190 students in Norway, comprising undergraduate business students and experienced public-sector employees enrolled in a Master of Public Administration (MPA) programme. Employing quantitative methods, including t-tests and correlation analysis, the study identifies significant differences in attitudes towards the public sector between these two groups, as well as between students aspiring to careers in the public versus the private sector. The public sector is generally perceived as more bureaucratic, less flexible, and less conducive to rapid career progression. By contrast, the private sector is associated with greater efficiency and enhanced individual career opportunities. In particular, access to a professional network is seen as highly advantageous in the private sector. These insights are especially relevant for policymakers and public-sector employers seeking to attract talent in an increasingly competitive labour market, particularly amid ongoing workforce shortages.